Dietary supplement use among adolescent athletes in Central Nebraska and their sources of information - Scofield, D. E.; Unruh, S. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to investigate the prevalence of dietary supplement use among adolescent athletes. The project was also directed at identifying the sources these student-athletes used for acquiring information about dietary supplements. One hundred thirty nine high school athletes (99 males; 34 females; mean age = 15.8 ± 1.19 years) volunteered to participate in this study. A 16-question anonymous survey instrument examined use of dietary supplements, reasons for use, type of sport participation, and sources of information regarding dietary supplements. Of the participants in this study, 22.3% (N = 31) reported currently taking dietary supplements. There was no relationship found between dietary supplement use and age. There were a significantly higher number of males reporting current dietary supplement use. Of those who reported to be currently taking dietary supplements, sports performance (N = 25) was the most reported reason for use. There were no significant differences found in reported dietary supplement use between any of the sports. Of the participants, 38.1% (N = 53) listed their coach as their best source of information on dietary supplements. The results of this study offer the current literature some additional insight into trends in supplement use among high school student athletes. Practical implications suggest that it may be necessary to ensure coaches have sufficient knowledge about dietary supplements so that adolescent athletes are receiving accurate information.